Mesin Pencacah Limbah Kulit Kakao - Moeso Andrianto; Fahriansyah Fahriansyah (Proklamasi 45 University, 2019)
Cocoa waste can still be used as something useful such as compost. The objective of this work is to make an organic waste crusher machine from cocoa waste. The method was the determination of systematic crushing, functional design, draw the crusher, making a prototype of the crusher machine, and performing functional test of the crusher. The crusher machine has been designed and provided. Functional tests conducted indicate that the machine can chop cocoa waste so that it can be further processed as compost.